2017
DOI: 10.1002/ccd.27347
|View full text |Cite
|
Sign up to set email alerts
|

Impact of flow, gradient, and left ventricular function on outcomes after transcatheter aortic valve replacement

Abstract: In patients undergoing TAVR, low flow was an independent predictor of 1-year mortality and HF, and a stronger predictor than either low AVG or LVEF. Patients with low flow and preserved EF had increased mortality and HF at 1-year, while those with low flow and reduced EF had outcomes similar to patients with normal flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…We suggest some probable factors affecting malnutrition 6 months post‐TAVR. LF‐LG AS, known as a state of progressed severe AS, is associated with higher mortality post‐TAVR (Carreras et al ., ; Kataoka, ; Tribouilloy et al ., ). The results of this study may not be robust considering the OR estimates and the CIs because of the small sample size and the low prevalence rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest some probable factors affecting malnutrition 6 months post‐TAVR. LF‐LG AS, known as a state of progressed severe AS, is associated with higher mortality post‐TAVR (Carreras et al ., ; Kataoka, ; Tribouilloy et al ., ). The results of this study may not be robust considering the OR estimates and the CIs because of the small sample size and the low prevalence rate.…”
Section: Discussionmentioning
confidence: 99%
“…Since malnutrition is associated with poor outcomes (Barr & Schumacher, 2003), and malnutrition might consequently relate to decreased QOL or mortality because of frailty syndrome, we also collected the following data on known predictors of poor outcomes in QOL and mortality post-TAVR (Arnold et al, 2014;Carreras et al, 2018;Hermiller, 2016;Kataoka, 2018;Puls et al, 2014;Reynolds, 2011;Schoenenberger et al, 2013;Shimura, 2017;Tribouilloy et al, 2015): disease information (classification of the New York Heart Association; left ventricular ejection fraction, %; mean pressure gradient [mean PG]: ≤40.0 mm Hg, severe; aortic valve area [AVA]: ≤1.0 cm 2 , severe; peak flow velocity [V max ]: ≤4.0 m/s, severe), diagnosed LF-LG AS (Hachicha, Dumesnil, Bogaty, & Pibarot, 2007), mortality risk score using the Society of Thoracic Surgeons score (high risk: ≤10%), physical function status (5-m gait speed, sec/5 m), basic activities of daily living (ADL) and the Katz Index of Independence in ADL (Shelkey & Wallace, 2000), frailty status (Clinical Frailty Scale [CFS]; frailty: ≥5) (Rockwood et al, 2005), and cognitive functional status (Mini-Mental State Examination [MMSE]; normal, ≥24) (Mitchell, 2009). These assessment tools have widely confirmed reliability and validity.…”
Section: Follow-up Participants At 1 Pom N = 56mentioning
confidence: 99%
“…The ROC curves showed that the ERS had the widest significant sensitivity-specificity AUC predicting all-cause or cardiovascular mortality and, even, the multivariable forward stepwise logistic regression analysis selected the ERS as the most significant risk factor of the all-cause or cardiovascular mortality and it excluded the ejection fraction or stroke volume index as risk factors, which are the usual markers with the more reliable level of predictively. 14 17 …”
Section: Discussionmentioning
confidence: 99%
“…This actual retrospective study sought to investigate the possible utility of ERS in TAVR patients’ selection. Briefly, we hypothesized that an increased ERS could be able to help the physician in identifying those patients with irreversible ventricular damage 14 17 and, accordingly, help to predict a poor survival and, hence, a TAVR futility. To verify this hypothesis, we calculated the pre-procedural ERS in a cohort of patients who underwent TAVR and collected the overall and cardiovascular mortality data after 1-year follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…However, transcatheter aortic valve implantation (TAVI) does not increase mortality or heart failure readmissions [ 3 , 4 ]. Moreover, patients with reduced LV function obtain better outcomes from TAVI compared to patients with preserved LV function [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%